Characterizations of multinomial distributions based on conditional distributions - Khoan T. Dinh; Truc T. Nguyen; Yining Wang (International Journal of Mathematics and Mathematical Sciences)
Several characterizations of the joint multinomial distribution of two discrete random vectors are derived assuming conditional multinomial distributions.